“Metal oxide -based heterostructures for gas sensors”- A review - Zappa, Dario; Galstyan, Vardan; Kaur, Navpreet; Munasinghe Arachchige, Hashitha M.M.; Sisman, Orhan; Comini, Elisabetta (Analytica chimica acta, 2018)
This review focuses on the synthesis and chemical sensing characterization of metal oxide heterostructures reported since 2012. Heterostructures exhibit strong interactions between closely packed interfaces, showing superior performances compared to single structures. Surface effects appear thanks to the magnification of nanostructures’ surface leading to an enhancement of surface related properties (the base of chemical sensors working mechanism). The combination of different metal oxides to form heterostructures further improves the selectivity and/or other important sensing parameters. A very large number of different morphologies and structures have been proposed, each one exhibiting peculiar sensing properties towards specific chemical compounds. Among the different preparation methodologies, a significant number has been performed by means of hydrothermal method. However, the combination of various fabrication methods seems a very efficient strategy to obtain metal oxide-based heterostructures with different morphologies and dimensions such as core-shell nanostructures, one-dimensional heterostructures, two-dimensional layered heterojunctions, and three-dimensional hierarchical heterostructures. Despite all extraordinary advances in both material science and nanotechnology and the results achieved with heterostructured chemical sensors, there are few points that still deserve further studies and investigations, such as possible diffusion across the junctions, reproducibility of the fabrication process, synergistic or catalytic effects among the materials forming the heterostructures and influence/stability of the contacts. Moreover, perfect control over their growth is mandatory for their application in commercial devices. Only a careful understanding of the growth and the interface properties could fill the existing gap between laboratory studies and real-world exploitation of these heterostructures. [Display omitted] •Resumes the advantages of properties of metal oxide heterojunctions.•Overviews recent studies on metal oxide heterostructure-based gas sensor.•Highlight progresses and summarizes the data on gas sensing.•Critically proposes footprints of future research and application trends in this field.